2017
DOI: 10.3390/molecules22071227
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Purification of Bergamottin from Citrus grandis (L.) Osbeck cv. Yongjiazaoxiangyou and Its Antiproliferative Activity and Effect on Glucose Consumption in HepG2 cells

Abstract: Bergamottin is a natural furanocoumarin compound with weak polarity. Characterization and quantification of bergamottin were carried out in different fruit tissues of various citrus cultivars. Among the four citrus tissues tested, i.e., flavedo, albedo, segment membrane (SM), and juice sacs (JS) in eight citrus cultivars, the highest bergamottin content was found in the flavedo of Citrus grandis (L.) Osbeck cv. Yongjiazaoxiangyou (YJZXY, 666.54 μg·g−1 DW). A combination of silica gel column chromatography and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 38 publications
4
10
0
1
Order By: Relevance
“…The anti-proliferative activity of bergamottin against promyelocytic leukemia HL-60 cells has also previously been reported by our group [58,59]. We observed that the combination of bergamottin and simvastatin produced synergistic effects on the tumor necrosis factor (TNF)-induced cytotoxicity and apoptosis in human chronic myelogenous leukemia KBM-5 cells.…”
Section: Bergamottin and Cancersupporting
confidence: 79%
See 1 more Smart Citation
“…The anti-proliferative activity of bergamottin against promyelocytic leukemia HL-60 cells has also previously been reported by our group [58,59]. We observed that the combination of bergamottin and simvastatin produced synergistic effects on the tumor necrosis factor (TNF)-induced cytotoxicity and apoptosis in human chronic myelogenous leukemia KBM-5 cells.…”
Section: Bergamottin and Cancersupporting
confidence: 79%
“…The anti-proliferative activity of bergamottin against human liver cancer HepG2 cells and gastric cancer BGC-823 cells has also been reported [59]. The cytotoxic effect of bergamottin on gastric cancer NCI-N87 cells has also been reported [65].…”
Section: Bergamottin and Cancermentioning
confidence: 99%
“…As far as we know, this is the first report about the anticancer activity of bergamottin toward HeLa cells. As shown in previous reports, although BM showed an inhibition effect on many cancer cell lines, such as HT-1080 fibrosarcoma [17], U266 multiple myeloma [18], HepG2 liver cancer, BGC-823 gastric cancer, HL-60 promyelotic leukemia [38], and A549 lung cancer cells [16], we did not observe BM to be significantly cytotoxic toward the HeLa cell line. Nevertheless, the insertion of a nitroxide moiety (10, IC 50.…”
Section: Discussionsupporting
confidence: 71%
“…HSCCC (TBE-300A, Shanghai Tauto Biotech. Co., Ltd., Shanghai, China) was used for further purification of nobiletin, tangeretin, and 5-demethylnobiletin from the PMF fraction according to our previous publication [21] with some modifications. Partition coefficients ( K value) of the three PMF monomers in different ratios of solutions were calculated, and the K value was used for selecting the two-phase solvent system.…”
Section: Methodsmentioning
confidence: 99%